Environmental conditions associated with carbonate-bearing rocks in lower Hawksbill Gap, Jezero western fan, Mars - Rebecca M.E. Williams; Joel A. Hurowitz; Linda C. Kah; Gwénaël Caravaca; Sanjeev Gupta; Nicolas Mangold; Michelle E. Minitti; R. Aileen Yingst; Kyle Uckert; Roger C. Wiens; Michael Tice; Megan Kennedy Wu; et al. (Icarus, 2026)

10 keV electron irradiation of methane ices at ocean world surface temperatures - Michael S. Bramble; Kevin P. Hand (Icarus, 2024)

Topography formation driven by sublimation of pure species on icy airless worlds - Antonio Macias Canizares; Daniel F. Berisford; David Goldstein; Philip Varghese; Laurence Trafton; Jordan Steckloff; Kevin P. Hand (Icarus, 2024)

Authors’ Response: Call for Standardized Language and Training to Bridge the Appraise/Apply Gap in Evidence-Based Dietetics Practice - Rosanna P. Watowicz; Rosa K. Hand (Journal of the Academy of Nutrition and Dietetics, 2024)

Call for Standardized Language and Training to Bridge the Appraise/Apply Gap in Evidence-Based Dietetics Practice - Rosanna P. Watowicz; Rosa K. Hand (Journal of the Academy of Nutrition and Dietetics, 2023)

Identification of genetic loci in lettuce mediating quantitative resistance to fungal pathogens - Harry Pink; Adam Talbot; Abi Graceson; Juliane Graham; Gill Higgins; Andrew Taylor; Alison C. Jackson; Maria Truco; Richard Michelmore; Chenyi Yao; Frances Gawthrop; David Pink; et al. (Theoretical and Applied Genetics, 2022)
Key message We demonstrate genetic variation for quantitative resistance against important fungal pathogens in lettuce and its wild relatives, map loci conferring resistance and predict key molecular mechanisms using transcriptome profiling. Abstract Lactuca sativa L. (lettuce) is an important leafy vegetable crop grown and consumed globally. Chemicals are routinely used to control major pathogens, including the causal agents of grey mould ( Botrytis cinerea ) and lettuce drop ( Sclerotinia sclerotiorum ) . With increasing prevalence of pathogen resistance to fungicides and environmental concerns, there is an urgent need to identify sources of genetic resistance to B. cinerea and S. sclerotiorum in lettuce. We demonstrated genetic variation for quantitative resistance to B. cinerea and S. sclerotiorum in a set of 97 diverse lettuce and wild relative accessions, and between the parents of lettuce mapping populations. Transcriptome profiling across multiple lettuce accessions enabled us to identify genes with expression correlated with resistance, predicting the importance of post-transcriptional gene regulation in the lettuce defence response. We identified five genetic loci influencing quantitative resistance in a F 6 mapping population derived from a Lactuca serriola (wild relative) × lettuce cross, which each explained 5–10% of the variation. Differential gene expression analysis between the parent lines, and integration of data on correlation of gene expression and resistance in the diversity set, highlighted potential causal genes underlying the quantitative trait loci.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Anatomical and biochemical studies of Spartium junceum infected by Xylella fastidiosa subsp. multiplex ST 87 - S. Falsini; C. Tani; G. Sambuco; A. Papini; P. Faraoni; S. Campigli; L. Ghelardini; G. Bleve; D. Rizzo; M. Ricciolini; I. Scarpelli; L. Drosera; et al. (Protoplasma, 2022)
Spartium junceum L. is a typical species of Mediterranean shrubland areas, also grown in gardens and parks as an ornamental. In recent years in Europe, S. junceum has been recurrently found to be infected by different subspecies and genotypes of the quarantine regulated bacterium Xylella fastidiosa (Xf). This work presents for the first time the anatomy of S. junceum plants that we found, by means of genetic and immunochemistry analysis, to be naturally infected by Xf subsp. multiplex ST87 (XfmST87) in Monte Argentario (Grosseto, Tuscany, Italy), a new outbreak area within the EU. Our anatomical observations showed that bacteria colonized exclusively the xylem conductive elements and moved horizontally to adjacent vessels through pits. Interestingly, a pink/violet matrix was observed with Toluidine blue staining in infected conduits indicating a high content of acidic polysaccharides. In particular, when this pink-staining matrix was observed, bacterial cells were either absent or degenerated, suggesting that the matrix was produced by the host plant as a defense response against bacterial spread. In addition, a blue-staining phenolic material was found in the vessels and, at high concentration, in the pits and inter-vessels. SEM micrographs confirmed that polysaccharide and phenolic components showed different structures, which appear to be related to two different morphologies: fibrillary and granular, respectively. Moreover, our LM observations revealed bacterial infection in xylem conductive elements of green shoots and leaves only, and not in those of other plant organs such as roots and flowers.

Assembly and characterisation of a unique onion diversity set identifies resistance to Fusarium basal rot and improved seedling vigour - Andrew Taylor; Graham R. Teakle; Peter G. Walley; William E. Finch-Savage; Alison C. Jackson; Julie E. Jones; Paul Hand; Brian Thomas; Michael J. Havey; David A. C. Pink; John P. Clarkson (Theoretical and Applied Genetics, 2019)
Key message A unique, global onion diversity set was assembled, genotyped and phenotyped for beneficial traits. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers. Abstract Conserving biodiversity is critical for safeguarding future crop production. Onion ( Allium cepa L.) is a globally important crop with a very large (16 Gb per 1C) genome which has not been sequenced. While onions are self-fertile, they suffer from severe inbreeding depression and as such are highly heterozygous as a result of out-crossing. Bulb formation is driven by daylength, and accessions are adapted to the local photoperiod. Onion seed is often directly sown in the field, and hence seedling establishment is a critical trait for production. Furthermore, onion yield losses regularly occur worldwide due to Fusarium basal rot caused by Fusarium oxysporum f. sp. cepae . A globally relevant onion diversity set, consisting of 10 half-sib families for each of 95 accessions, was assembled and genotyping carried out using 892 SNP markers. A moderate level of heterozygosity (30–35%) was observed, reflecting the outbreeding nature of the crop. Using inferred phylogenies, population structure and principal component analyses, most accessions grouped according to local daylength. A high level of intra-accession diversity was observed, but this was less than inter-accession diversity. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers, confirming the utility of the diversity set for discovering beneficial traits. The onion diversity set and associated trait data therefore provide a valuable resource for future germplasm selection and onion breeding.

Pomegranate dieback caused by Lasiodiplodia gilanensis in California - J. R. Úrbez-Torres; F. Peduto Hand; F. P. Trouillas; W. D. Gubler (European Journal of Plant Pathology, 2017)

Accounting for adaptive capacity and uncertainty in assessments of species’ climate‐change vulnerability - Alisa A. Wade; Brian K. Hand; Ryan P. Kovach; Gordon Luikart; Diane C. Whited; Clint C. Muhlfeld (Conservation Biology, 2017)
Climate‐change vulnerability assessments (CCVAs) are valuable tools for assessing species’ vulnerability to climatic changes, yet failure to include measures of adaptive capacity and to account for sources of uncertainty may limit their effectiveness. We took a more comprehensive approach that incorporates exposure, sensitivity, and capacity to adapt to climate change. We applied our approach to anadromous steelhead trout ( Oncorhynchus mykiss ) and nonanadromous bull trout ( Salvelinus confluentus ), threatened salmonids within the Columbia River Basin (U.S.A.). We quantified exposure on the basis of scenarios of future stream temperature and flow, and we represented sensitivity and capacity to adapt to climate change with metrics of habitat quality, demographic condition, and genetic diversity. Both species were found to be highly vulnerable to climate change at low elevations and in their southernmost habitats. However, vulnerability rankings varied widely depending on the factors (climate, habitat, demographic, and genetic) included in the CCVA and often differed for the 2 species at locations where they were sympatric. Our findings illustrate that CCVA results are highly sensitive to data inputs and that spatial differences can complicate multispecies conservation. Based on our results, we suggest that CCVAs be considered within a broader conceptual and computational framework and be used to refine hypotheses, guide research, and compare plausible scenarios of species’ vulnerability to climate change.

Assessments of species’ vulnerability to climate change: from pseudo to science - Alisa A. Wade; Brian K. Hand; Ryan P. Kovach; Clint C. Muhlfeld; Robin S. Waples; Gordon Luikart (Biodiversity and Conservation, 2017)

Identification and Functional Prediction of Large Intergenic Noncoding RNAs (lincRNAs) in Rainbow Trout (Oncorhynchus mykiss) - Jian Wang; Liyuan Fu; Prasanthi P. Koganti; Lei Wang; Jacqelyn M. Hand; Hao Ma; Jianbo Yao (Marine Biotechnology, 2016)

Climate variables explain neutral and adaptive variation within salmonid metapopulations: the importance of replication in landscape genetics - Brian K. Hand; Clint C. Muhlfeld; Alisa A. Wade; Ryan P. Kovach; Diane C. Whited; Shawn R. Narum; Andrew P. Matala; Michael W. Ackerman; Brittany A. Garner; John S. Kimball; Jack A. Stanford; Gordon Luikart (Molecular Ecology, 2016)
Understanding how environmental variation influences population genetic structure is important for conservation management because it can reveal how human stressors influence population connectivity, genetic diversity and persistence. We used riverscape genetics modelling to assess whether climatic and habitat variables were related to neutral and adaptive patterns of genetic differentiation (population‐specific and pairwise F ST ) within five metapopulations (79 populations, 4583 individuals) of steelhead trout ( Oncorhynchus mykiss ) in the Columbia River Basin, USA . Using 151 putatively neutral and 29 candidate adaptive SNP loci, we found that climate‐related variables (winter precipitation, summer maximum temperature, winter highest 5% flow events and summer mean flow) best explained neutral and adaptive patterns of genetic differentiation within metapopulations, suggesting that climatic variation likely influences both demography (neutral variation) and local adaptation (adaptive variation). However, we did not observe consistent relationships between climate variables and F ST across all metapopulations, underscoring the need for replication when extrapolating results from one scale to another (e.g. basin‐wide to the metapopulation scale). Sensitivity analysis (leave‐one‐population‐out) revealed consistent relationships between climate variables and F ST within three metapopulations; however, these patterns were not consistent in two metapopulations likely due to small sample sizes ( N = 10). These results provide correlative evidence that climatic variation has shaped the genetic structure of steelhead populations and highlight the need for replication and sensitivity analyses in land and riverscape genetics.

Genetic diversity is related to climatic variation and vulnerability in threatened bull trout - Ryan P. Kovach; Clint C. Muhlfeld; Alisa A. Wade; Brian K. Hand; Diane C. Whited; Patrick W. DeHaan; Robert Al‐Chokhachy; Gordon Luikart (Global Change Biology, 2015)
Understanding how climatic variation influences ecological and evolutionary processes is crucial for informed conservation decision‐making. Nevertheless, few studies have measured how climatic variation influences genetic diversity within populations or how genetic diversity is distributed across space relative to future climatic stress. Here, we tested whether patterns of genetic diversity (allelic richness) were related to climatic variation and habitat features in 130 bull trout ( Salvelinus confluentus ) populations from 24 watersheds (i.e., ~4–7th order river subbasins) across the Columbia River Basin, USA . We then determined whether bull trout genetic diversity was related to climate vulnerability at the watershed scale, which we quantified on the basis of exposure to future climatic conditions (projected scenarios for the 2040s) and existing habitat complexity. We found a strong gradient in genetic diversity in bull trout populations across the Columbia River Basin, where populations located in the most upstream headwater areas had the greatest genetic diversity. After accounting for spatial patterns with linear mixed models, allelic richness in bull trout populations was positively related to habitat patch size and complexity, and negatively related to maximum summer temperature and the frequency of winter flooding. These relationships strongly suggest that climatic variation influences evolutionary processes in this threatened species and that genetic diversity will likely decrease due to future climate change. Vulnerability at a watershed scale was negatively correlated with average genetic diversity ( r = −0.77; P 0.001); watersheds containing populations with lower average genetic diversity generally had the lowest habitat complexity, warmest stream temperatures, and greatest frequency of winter flooding. Together, these findings have important conservation implications for bull trout and other imperiled species. Genetic diversity is already depressed where climatic vulnerability is highest; it will likely erode further in the very places where diversity may be most needed for future persistence.

Projected changes in hailstorms during the 21st century over the UK - M. G. Sanderson; W. H. Hand; P. Groenemeijer; P. M. Boorman; J. D. C. Webb; L. J. McColl (International Journal of Climatology, 2015)
Hailstorms can pose a significant threat to society, by damaging property and disrupting livelihoods. An understanding of how hailstorm characteristics may change under a warming climate is therefore important for assessing the risk of hail damage for the insurance industry. A simple model of hailstone formation has been driven using meteorological data produced by a regional climate model (RCM) to project how hailstorm numbers and hailstone sizes could change during the 21st century in the UK . Evaluation of the modelled hailstone sizes, numbers and spatial distributions showed that they agreed reasonably well with observations. The effect of climate change on the numbers of damaging hailstorms in the UK (hailstones with diameters greater than 15 mm) was then investigated. A downward trend in the total number of damaging hailstorms during the 21st century was projected, with statistically significant trends for hailstones with diameters between 21 and 50 mm. Melting of hailstones made little contribution to the projected reductions. The results are subject to large uncertainties, some of which originate with the convective parameterization scheme used by the climate model.

Early Mesoproterozoic metamorphism in the Barossa Complex, South Australia: links with the eastern margin of Proterozoic Australia - L. J. Morrissey; M. Hand; B. P. Wade; M. Szpunar (Australian Journal of Earth Sciences, 2013)

Assessment of Motor Functioning in the Preschool Period - Jan P. Piek; Beth Hands; Melissa K. Licari (Neuropsychology Review, 2012)

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

High-grade Paleoproterozoic reworking in the southeastern Gawler Craton, South Australia ∗ - R. Dutch; M. Hand; P. D. Kinny (Australian Journal of Earth Sciences, 2008)

Origin of metasedimentary and igneous rocks from the Entia Dome, eastern Arunta region, central Australia: a U – Pb LA-ICPMS, SHRIMP and Sm – Nd isotope study - B. P. Wade; M. Hand; D. W. Maidment; D. F. Close; I. R. Scrimgeour (Australian Journal of Earth Sciences, 2008)

Temporal constraints on the timing of high-grade metamorphism in the northern Gawler Craton: implications for assembly of the Australian Proterozoic - J. L. Payne; M. Hand; K. M. Barovich; B. P. Wade (Australian Journal of Earth Sciences, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Identification of quantitative trait loci for resistance to Xanthomonas campestris pv. campestris in Brassica rapa - P. Soengas; P. Hand; J. G. Vicente; J. M. Pole; D. A. C. Pink (Theoretical and Applied Genetics, 2007)